TRAVEL PATTERN WISATAWAN SELAMA PANDEMI COVID-19 - Retnaningtyas Susanti; sulis purwanto; Sukma Yudistira; Yuke Permata Lisna (JURNAL PENDIDIKAN DAN KELUARGA, 2021)
The COVID-19 pandemic that has hit the world, including Indonesia, has had a crucial influence on the tourism industry. It is undeniable that the tourism industry in Indonesia seems to be in suspended animation due to unpreparedness for this disaster. From the supply side, tourism entrepreneurs are overwhelmed because of the absence of visits due to flight closures, travel minimization, and strict rules regarding the closure of tourist attractions during 2019. From the demand side, the community's need for tourism remains high, interest in traveling is even greater after one year "at home". In mid-2020 when tourism policies began to be relaxed, there was a revival of this industry's revival. There has been a change in tourist travel patterns during this pandemic, not just looking for beautiful tourist attractions, but also safe areas. The research that has been done shows that the pattern of tourist visits changes, there is an adaptation to the pandemic conditions. In-depth interviews were conducted on informants to obtain accurate data, tourists and tourist attraction managers were key informants. Some of the changes include: use of vehicles, selection of locations that offer health protocols, and expenses